Skull Ganglioneuroblastoma: A Case Report - ARIEF, M RADHIAN; ASHARI, SAMSUL; MAHYUDDIN, HILMAH (Indonesian Journal of Cancer, 2010)
Ganglioneuromas and ganglioneuroblastomas are tumors of the sympathetic nervous system that originate from neural crest sympathogonia, which are completely undifferentiated cells of the sympathetic nervous system. Along with neuroblastomas, ganglioneuromas and ganglioneuroblastomas are collectively known as neuroblastic or neurogenic tumors. Ganglioneuroblastoma is an intermediate tumor, a tumor that is between benign (slow-growing and unlikely to spread) and malignant (fast-growing, aggressive, and likely to spread). We report a rare case of skull ganglioneuroblastoma in a 4 months old child who came with a progressive increasing mass volume in the forehead. No other neurologic deficit was found. Serial Brain CT Scan was performed and showed progressive increasing of the mass volume. Comprehensive management was carry out for this patient.